ChemInform Abstract: Enantioselective Synthesis and Application to the Allylic Imidate Rearrangement of Amine‐Coordinated Palladacycle Catalysts of Cobalt Sandwich Complexes. Issue 22 (3rd June 2014) - Cassar, Doyle J.; Ilyashenko, Gennadiy; Ismail, Muhammad; Woods, James; Hughes, David L.; Richards, Christopher J.
Abstract The enantioselective palladation of amine substrates followed by enantioselective transcyclopalladation enables the synthesis of ferrocene‐based phosphapalladacycles with good enantiomeric excess.